LEXICAL BORROWINGS FROM TURKIC AND PERSIAN LANGUAGES IN EMBASSY BOOKS ON RUSSIA'S RELATIONS WITH KHIVA AND BUKHARA IN THE 17TH CENTURY: SOURCE STUDIES AND LINGUOCULTURAL ASPECTS (American Journal of Pedagogical and Educational Research, 2026)
The article presents a comprehensive linguistic analysis of lexical borrowings from Turkic (turki) and Persian (farsi) languages recorded in unpublished embassy books on Russia's relations with Khiva (1670–1673, 1682–1684) and Bukhara (1669–1675), stored in the Russian State Archive of Ancient Acts (RGADA). The study is conducted within the framework of linguistic source studies and cultural linguistics. Based on extensive factual material (more than 400 lexical units of Eastern origin), thematic groups of borrowings are identified, and mechanisms of their phonetic and morphological adaptation in Russian business texts are described. It is established that Eastern vocabulary in embassy books reflects the realities of the diplomatic, commercial and cultural life of the Central Asian–Russian intercultural space of the 17th century. A number of lexical units not recorded in historical dictionaries of the Russian language have been introduced into scientific circulation. The results obtained make a significant contribution to historical lexicology, contact linguistics, and linguistic source studies.